Exposição a pesticidas em abelhas (Apis mellifera L.) utilizadas na polinização do melão (Cucumis melo L.) - Silva, Idalécio Pacífico da (Universidade Federal Rural do Semi-Árido, 2015)
Pollinators are among the essential components for the functioning of ecosystems in general, because it is essential for the reproduction and maintenance of the diversity of plant species and provide food for humans and animals, also influencing the qualitative aspect of the production. Currently, the population density of many pollinators are being reduced to levels that can impair pollination services. The decline of honeybee Africanized (Apis mellifera L.) populations impacts global agricultural production and has a clear impact on both food production and the economy. One of the probable causes for this decline is the indiscriminate use of pesticides. Thus, there was comparative levels of exposure to pesticides among bees (Apis mellifera L.) that are used to pollinate melon crops, bees (Apis mellifera L.) kept in the bush, and Jandaira bees (Melipona subnitida ) kept in the bush. To do this, honey samples were collected from 23 colonies of Apis mellifera used to pollinate melon palntações, 20 colonies of Apis mellifera foraging forest and 10 colonies of Melipona subnitida foraging in the forest. The level of exposure to pesticides was determined by measuring the residual levels of 152 compounds in honey using a multiresidue analysis technique in UFLC-MS system. Honey samples from the present study contained 19 different pesticides, 13 of which were present in honey from bees pollinating melon crops. The levels of some compounds were sufficiently high to promote adverse effects in the bees. Thus, crop pollination offers a great toxicological risk to bees that may contribute to colony collapse
Pesticide exposure of honeybees (Apismellifera L.)pollinating melon crops
Keywords: Contaminação ambiental; Inseticidas; Acaricidas; Herbicidas; Fungicidas; Nematicidas; Análise multiresíduos; Mel; Environmental contamination; Insecticides; Acaricides; Herbicides; Fungicides; Nematicides; Multiresidue analysis; Honey; CIENCIAS AGRARIAS::MEDICINA VETERINARIA